Status Gizi dengan Kejadian ISPA Balita di Wilayah Kerja Puskesmas Unyur Kota Serang Sebelum dan Selama Pandemi Covid-19: Nutritional Status and the Acute Respiratory Infection Incidence in Toddlers in the Work Area of the Unyur Health Center of Serang City Before and During the Covid-19 Pandemic - Nurjamillah, Sanni Yasmi; Dwiriani, Cesilia Meti (Jurnal Ilmu Gizi dan Dietetik, 2022)
This study aims to analyze the relationship between the nutritional status of toddlers and the incidence of Acute Respiratory Infection (ARI) in toddlers in the work area of Unyur Health Center of Serang City work area before and during the Covid-19 pandemic. The research design is a cross-sectional comparative using secondary data from the Integrated Management of Childhood Illness (IMCI) at the health center in 2019-2020. The study analyzes toddler data obtained by systematic sampling. The data analyzed were toddler characteristics, immunization status, nutritional status, and ARI incidents in toddlers. Spearman's correlation test results showed no association between characteristics, immunization status, and nutritional status (p>0.05) and the incidence of ARI and its severity in toddlers before and during the Covid-19 pandemic.